2019
DOI: 10.1590/18069657rbcs20170413
|View full text |Cite
|
Sign up to set email alerts
|

Digital Soil Mapping of Soil Properties in the “Mar de Morros” Environment Using Spectral Data

Abstract: Quantification of soil properties is essential for better understanding of the environment and better soil management. The conventional techniques of laboratory analysis are sometimes costly and detrimental to the environment. Thus, development of new techniques for soil analysis that do not generate residues, such as spectroscopy, is increasingly necessary as a viable way to estimate a wide range of soil properties. The objective of this study was to predict the levels of organic carbon (OC), clay, and extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Furthermore, the relationship between the covariates and BAC of PTEs in soil-rice systems is highly complex and difficult to model using linear relations alone, which further lower the performance of MLR. SVMs have also previously been employed to predict soil SOC stock [84], phosphorus [85], and clay [85]. They were reported to be more suitable for classification than quantitative prediction [86].…”
Section: Model Performance Employing the Different Methods And Elementsmentioning
confidence: 99%
“…Furthermore, the relationship between the covariates and BAC of PTEs in soil-rice systems is highly complex and difficult to model using linear relations alone, which further lower the performance of MLR. SVMs have also previously been employed to predict soil SOC stock [84], phosphorus [85], and clay [85]. They were reported to be more suitable for classification than quantitative prediction [86].…”
Section: Model Performance Employing the Different Methods And Elementsmentioning
confidence: 99%
“…Although parental material is critical in the soil texture spatial distribution, the covariates selection identified that the et al, 2014) or based on the spectral response in the visible and near-infrared spectrum (Vis-NIR), medium infrared (MIR), and Vis-NIR-MIR (Campbell et al, 2019). In the PSF predictions (in specific, the ALR components), the importance of the climatic covariates did not have apparent changes with depth.…”
Section: Discussionmentioning
confidence: 99%
“…Juiz de Fora (21º41'20" S and 43º20'40" W) is a medium-sized municipality with 573.285 inhabitants (IBGE, 2020) located in the southeast of the state of Minas Gerais, Brazil, in the geographical mesoregion of Zona da Mata (Figure 1). It is situated in a landform called Mar de Morros, which is characterized by a large number of hills and valleys at altitudes ranging from 600 to 1000 msm, where are found clayey soils, mostly of the Latosol type, with high levels of organic carbon (NUNES et al, 2001;CAMPBELL et al, 2019). The climate has a welldefined seasonality, classified as subtropical in altitude (Cwa, sensu Köeppen) defined by two distinct seasons, with lower temperatures and precipitation between the months of May to September, and warmer and with greater precipitation between october and April.…”
Section: Study Areamentioning
confidence: 99%